IMPLEMENTASI MODUL AJAR BERDIFERENSIASI DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA PENAJAM PASER UTARA - Firdaus, Mohamad; Jannah, Fathul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of differentiated learning modules in improving student motivation and learning outcomes in Islamic Religious Education and Character Education at Penajam Paser Utara Senior High School. This study used a descriptive qualitative approach with observation, interview, and documentation techniques. The results showed that differentiated learning can significantly improve student motivation, independence, and learning outcomes. The results showed that the implementation of differentiated modules at SMAN 2, 3, and 5 PPU effectively increased intrinsic motivation, independence, and student learning completion. This was achieved through adapting instructions that were responsive to diverse learning styles and providing autonomy to students in the learning process. This strategy successfully synergized academic achievement with character transformation and student spiritual awareness through the use of varied media, flexible assessment, and adaptive teacher intervention. Overall, the implementation of this module was proven to be able to shape student profiles that are not only cognitively superior, but also possess spiritual depth and strong character in accordance with the principles of the Independent Curriculum.